On the history of bus service in pre-revolutionary Kiev - Машкевич, С. (Київський національний університет імені Тараса Шевченка, 2013)
The article is dedicated to an unfamiliar episode of Kiev history – passenger bus service which existed in that city in 1913-14. The main motivation was to provide competition for the private tram enterprise, thereby reducing its profit and bringing down its price pending its buyout by the city.

Розглядається маловідомий епізод історії Києва – влаштування пасажирського автобусного сполучення в 1913-14 роках, що мало метою створення конкуренції трамваю та здешевлення приватного трамвайного підприємства напередодні його викупу містом.
До історії автобусного сполучення в дореволюційному Києві
Keywords: Kiev; public transportation; bus; Київ; міський транспорт; автобус